1992
DOI: 10.1128/aem.58.9.2933-2937.1992
|View full text |Cite
|
Sign up to set email alerts
|

Initial hydrogenation during catabolism of picric acid by Rhodococcus erythropolis HL 24-2

Abstract: Rhodococcus erythropolis HL 24-2, which was originally isolated as a 2,4-dinitrophenol-degrading bacterium, could also utilize picric acid as a nitrogen source after spontaneous mutation. During growth, the mutant HL PM-1 transiently accumulated an orange-red metabolite, which was identified as a hydride-Meisenheimer complex of picric acid. This complex was formed as the initial metabolite and further converted with concomitant liberation of nitrite. 2,4,6-Trinitrocyclohexanone was identified as a dead-end met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 16 publications
5
52
0
Order By: Relevance
“…Thus, hydride and dihydride complexes have been identified as initial metabolites (23,27). In addition, the identification of 2,4dinitrophenol (2,4-DNP) and 4,6-dinitrohexanoate (4,6-DNH) (13,14,23,22) as metabolites of picrate indicates that extensive hydrogenation of the aromatic system (6 H per mol of picrate and 4 H per mol of 2,4-DNP) gives rise to a nonoxygenolytic ring cleavage. As outlined in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, hydride and dihydride complexes have been identified as initial metabolites (23,27). In addition, the identification of 2,4dinitrophenol (2,4-DNP) and 4,6-dinitrohexanoate (4,6-DNH) (13,14,23,22) as metabolites of picrate indicates that extensive hydrogenation of the aromatic system (6 H per mol of picrate and 4 H per mol of 2,4-DNP) gives rise to a nonoxygenolytic ring cleavage. As outlined in Fig.…”
mentioning
confidence: 99%
“…As outlined in Fig. 1, transformation of picrate via a hydride -complex to 2,4-DNP and 4,6-DNH is considered part of a productive catabolic sequence in Rhodococcus erythropolis HL PM-1, whereas the dihydride complexes of trinitroaromatics are dead-end products (14,27).…”
mentioning
confidence: 99%
“…lb), the three nitro groups on TNT are removed as nitrite ions.13 Nitro group removal by these Pseudomonus strains is thought to be analogous to a similar reaction on picric acid by the bacterium, Rhodococcus erythropolis HL 24-2. 29 In this reaction, nitro group removal involves the formation of a hydride-Meisenheimer complex (Fig. 2).13, 29 Vorbeck et al 43 have recently reported conclusive evidence that a hydride-Meisenheimer complex is the initial metabolite in aerobic TNT bioconversion.…”
Section: Tnt Pathwaymentioning
confidence: 99%
“…29 In this reaction, nitro group removal involves the formation of a hydride-Meisenheimer complex (Fig. 2).13, 29 Vorbeck et al 43 have recently reported conclusive evidence that a hydride-Meisenheimer complex is the initial metabolite in aerobic TNT bioconversion. The main metabolic product, toluene, is recovered after all three nitro groups on TNT are removed.…”
Section: Tnt Pathwaymentioning
confidence: 99%
“…It was firstly reported by Kurane and later confirmed by Takeda et al that the main component of its MBF production is protein, which has been widely used in environmental pollution control and industrial wastewater treatment. The flocculant NOC-1 produced by R. erythropolis s-1 has a strong flocculation effect on livestock waste and sewage treatment, and it is currently recognized as one of the best flocculating bacteria (Alberts, Engelbrecht, Steyn, Holzapfel, & van, 2006;Izumi, Ohshiro, Ogino, Hine, & Shimao, 1994;Kurane et al, 1994;Kurane, Toeda, Takeda, & Suzuki, 1986;Lenke & Knackmuss, 1992;Peng et al, 2014;Takeda, Kurane, Koizumi, & Nakamura, 1991). Therefore, R. erythropolis was used as a reference in this study for evaluating the flocculation effect of bacterial strains.…”
mentioning
confidence: 99%